2022
DOI: 10.3390/ijms232214030
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variation Underlying the Breeding Selection of Quinoa Varieties Longli-4 and CA3-1 in China

Abstract: Quinoa (Chenopodium quinoa) is a well-known climate-resilient crop and has been introduced into multiple marginal lands across the world, including China, to improve food security and/or balanced nutrient supplies. Conventional breeding has been widely applied in the selection and breeding of quinoa varieties in China since 1980s; however, few studies have been implemented on the genetic variances among different varieties developed by diversity breeding objectives. In this study, the phenotypic and genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Hybridizing these introduced materials with local varieties increases the chances of genetic diversity in sugarcane, enhancing the population’s adaptability to different environmental conditions [ 66 ] and contributing to broader adaptability and improved growth performance in various regions [ 67 ]. Combining introduced germplasms with local varieties promotes the incorporation of beneficial genetic factors in the offspring, leading to improvements in specific traits [ 68 ], such as enhanced resistance to biotic and abiotic stressors in sugarcane [ 69 , 70 ]. Genetic improvement could achieve superior performance in multiple aspects of new varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridizing these introduced materials with local varieties increases the chances of genetic diversity in sugarcane, enhancing the population’s adaptability to different environmental conditions [ 66 ] and contributing to broader adaptability and improved growth performance in various regions [ 67 ]. Combining introduced germplasms with local varieties promotes the incorporation of beneficial genetic factors in the offspring, leading to improvements in specific traits [ 68 ], such as enhanced resistance to biotic and abiotic stressors in sugarcane [ 69 , 70 ]. Genetic improvement could achieve superior performance in multiple aspects of new varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. (2022) reported 16.7% heterozygosity for variety Longli‐4 by using SNPs. Our study confirmed a range of 4.9% and 21.9% and an average heteropoietic of 11.76% across all germplasms.…”
Section: Discussionmentioning
confidence: 99%
“…By using genome wide markers, we were able to estimate a range Crop Science of 4.9% and 21.9% for heterozygosity among these quinoa accessions. Li et al (2022) reported 16.7% heterozygosity for variety Longli-4 by using SNPs. Our study confirmed a range of 4.9% and 21.9% and an average heteropoietic of 11.76% across all germplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Today, C. quinoa is mainly cultivated in South America and Asia, and in China, it is grown primarily in Shanxi and Qinghai provinces, and the northwest of the country. It is noted as a particularly nutrient-rich grain crop and a valuable source of proteins, fat, minerals, vitamins, fiber, and other nutrients, the levels of which tend to be higher than those in more common cultivated grain crops ( 1 , 2 ). Quinoa is considered a whole-grain product containing a rich variety of bioactive substances, including phenols, saponins, and glucans, and can play potentially essential roles in the treatment of different diseases ( 3–5 ), based on the anti-oxidative, anti-cancer, anti-radiation, antibacterial and cholesterol metabolism-regulatory effects of its constituent ( 6 ).…”
Section: Quinoamentioning
confidence: 99%